2021
DOI: 10.1177/0894439320987569
|View full text |Cite
|
Sign up to set email alerts
|

Political Interaction Beyond Party Lines: Communication Ties and Party Polarization in Parliamentary Twitter Networks

Abstract: A growing body of research has examined the uptake of social media by politicians, the formation of communication ties in online political networks, and the interplay between social media and political polarization. However, few studies have analyzed how social media are affecting communication in parliamentary networks. This is especially relevant in highly fragmented political systems in which collaboration between political parties is crucial to win support in parliament. Does MPs’ use of social media foste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 67 publications
0
14
1
2
Order By: Relevance
“…As for the existence of status-homophily, in line with previous research in the field (Straus et al, 2013), our data reveal high levels of homophily among the mentions of young (26-44) Catalan MPs and young (26-44) Dutch MPs. However, in contrast to previous studies which found that gender similarity explained interactions in Twitter political networks (Esteve-Del-Valle et al, 2021;Karlsen & Ejolras, 2016), homophilous gender ties were only found to explain interactions among female MPs in the Netherlands. The same applies to the leadership position homophily among the MPs (holding a political position), which despite being found to explain the existence of followee relations among politicians (Esteve-Del-Valle & Bravo, 2018b), does not explain the existence of homophilous ties among the Catalan MPs or among the Dutch MPs.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As for the existence of status-homophily, in line with previous research in the field (Straus et al, 2013), our data reveal high levels of homophily among the mentions of young (26-44) Catalan MPs and young (26-44) Dutch MPs. However, in contrast to previous studies which found that gender similarity explained interactions in Twitter political networks (Esteve-Del-Valle et al, 2021;Karlsen & Ejolras, 2016), homophilous gender ties were only found to explain interactions among female MPs in the Netherlands. The same applies to the leadership position homophily among the MPs (holding a political position), which despite being found to explain the existence of followee relations among politicians (Esteve-Del-Valle & Bravo, 2018b), does not explain the existence of homophilous ties among the Catalan MPs or among the Dutch MPs.…”
Section: Discussioncontrasting
confidence: 99%
“…On Facebook, Wimmer and Lewis (2010) showed that racial homogeneity results from racial homophilic ties among users, and Barnett and Benefield (2015) found cultural homophily to be one of the causes of international Facebook friendship networks. Similarly, several studies conducted on Twitter have shown that communications among individuals with shared sociodemographic characteristics and political attitudes are more likely to happen than with dissimilar individuals (Esteve- Del-Valle et al, 2021;Himelboim et al, 2013;Hong & Kim, 2016).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our mobile, digital, and networked media create an environment in which connection is central (Esteve Del Valle et al, 2021;Esteve Del Valle et al, 2020a). In The Culture of Connectivity, José van Dijck (2013) demonstrates how the interconnectedness of social media platforms has given rise to a new 'ecosystem of connective media' that reshapes sociality into a 'platformed' sociality (pp.…”
Section: Memory Work and Social Mediamentioning
confidence: 99%
“…Tal y como han comentado varios autores en este ámbito, «la influencia de las redes sociales en política es cada vez mayor» (Renobell, 2017: 118). En este sentido, un creciente cuerpo de investigación ha examinado la adopción de las redes sociales por parte de los políticos, la formación de lazos de comunicación en las redes políticas en línea y la interacción entre las redes sociales y la polarización política (Esteve Del Valle et al, 2021).…”
Section: Introductionunclassified